f-Biharmonic and Bi-f-Harmonic Submanifolds of Product Spaces - Karaca , Fatma; Özgür, Cihan (Sarajevo Journal of Mathematics, 2017)
We consider f-biharmonic and bi-f-harmonic submanifolds of the product of two real space forms. We find the necessary and sufficient conditions for a submanifold to be f-biharmonic and bi-f-harmonic in a product of two real space forms.